Percutaneous transcatheter aortic disc valve prosthesis implantation: a feasibility study - Sochman, J; Peregrin, J H; Pavcnik, D; Timmermans, H; Rösch, J (Cardiovascular and interventional radiology, 2000)
PURPOSE: Over the past 30 years there have been experimental efforts at catheter-based management of aortic valve regurgitation with the idea of extending treatment to nonsurgical candidates. A new catheter-based aortic valve design is described. METHODS: The new catheter-delivered valve consists of a stent-based valve cage with locking mechanism and a prosthetic flexible tilting valve disc. The valve cage is delivered first followed by deployment and locking of the disc. In acute experiments, valve implantation was done in four dogs. RESULTS: Valve implantation was successful in all four animals. The implanted valve functioned well for the duration of the experiments (up to 3 hr). CONCLUSION: The study showed the implantation feasibility and short-term function of the tested catheter-based aortic disc valve. Further experimental studies are warranted.
Keywords: Prosthesis Design; stenty; psi; chirurgická náhrada chlopně; Stents; srdeční chlopně umělé; aortální insuficience; Animals; Feasibility Studies; protézy - design; Dogs; Heart Valve Prosthesis; zvířata; Aortic Valve Insufficiency; studie proveditelnosti; Heart Valve Prosthesis Implantation